2019
DOI: 10.1080/13683500.2019.1622656
|View full text |Cite
|
Sign up to set email alerts
|

Temporary resident evil? Managing diverse impacts of second-home tourism

Abstract: Second-home tourism is a popular form of tourism in many countries. Sweden has over 600,000 second homes and more than half of the population have access to such properties. Previous literature on second-home tourism indicates that it impacts local communities and municipalities in many different ways, ranging from public services and land-use planning to the housing market and the local economy. However, it has not been sufficiently investigated how, where and by which spatial patterns these impacts might com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 35 publications
1
13
0
5
Order By: Relevance
“…Our research shows that the town under study has taken important steps to manage multiculturality, even if older foreign residents hardly make any efforts to integrate into Spanish society, since they feel at ease living inside a “colony”; neither foreign residents nor tourists are seen as a nuisance by local residents. This result matches those obtained in previous studies about the impact of second‐home tourism (Back, ). Younger foreign residents do make an effort to fit into the local society and culturally enrich schools or work centers, though.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our research shows that the town under study has taken important steps to manage multiculturality, even if older foreign residents hardly make any efforts to integrate into Spanish society, since they feel at ease living inside a “colony”; neither foreign residents nor tourists are seen as a nuisance by local residents. This result matches those obtained in previous studies about the impact of second‐home tourism (Back, ). Younger foreign residents do make an effort to fit into the local society and culturally enrich schools or work centers, though.…”
Section: Discussionsupporting
confidence: 91%
“…The relationships between tourists, foreign residents, and the local population often face numerous problems. Furthermore, ignoring residential—or second‐home—tourism would mean leaving aside an important explanation of travel and tourism infrastructure behavior (Back, ; Honkanen, Pitkänen, & Hall, ; Müller, ); hence we are interested in learning more about local residents’ attitudes with regard to tourism as a whole and, more specifically, concerning residential tourism.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis centred on reoccurring patterns, similarities and differences between municipalities in the same second-home landscape and between municipalities in different second-home landscapes. Data on second-home tourism's impact on for example, public services, infrastructure, landuse planning and community was also collected during the interviews, but the analysis of that data is done separately from this study (see Back 2020).…”
Section: Interviewing Municipal Civil Servantsmentioning
confidence: 99%
“…Even in Sweden, the COVID-19 pandemic caused considerable debate. However, as Back (2020) recently revealed, many local jurisdictions lack knowledge of the number and use patterns of second homes. Departing from the notion it can be concluded that much of the ongoing debate has been based on occasional observations and more or less qualified guesses.…”
Section: Re-evaluating Rural Healthcare Capacities and Second Home Acmentioning
confidence: 99%